Standardization Paths for NGN IMS-Based Architecture - Tatiana Kovacikova; Pavol Segec; Michal Bruncko (Communications - Scientific letters of the University of Zilina, 2008)
Thanks to the rapid development of technology and increased availability of bandwidth, today more than ever, multiple services such as voice, video and data can be integrated and efficiently carried over a single infrastructure based on a packet network. An NGN (Next Generation Network) is able to deploy those services independently from underlying transport-related technologies, giving fixed or mobile users an access to different providers with the adequate QoS and security. In fact, it is the IMS (IP Multimedia Subsystem) inside the NGN that enables and drives efficient converged service offerings. IMS provides the framework for a common service and session control layer standardized on IP, with SIP controlling all media sessions. The IMS standardization breaks down all the functions necessary to support multimedia applications and to provide standardized (open) interfaces towards application servers enabling enhanced premium services as well as the interworking with other (legacy) networks such as the PSTN/PLMN (Public Switched Telephone Network/Public Land Mobile Network. The paper is describing the current state of the art in the NGN standardization within the ETSI and related standardization bodies.